The importance of physical function as a clinical outcome: Assessment and enhancement - O'Neill, Deirdre; Forman, Daniel E. (Clinical cardiology (Mahwah, N.J.), 2020)
The burgeoning population of older adults is intrinsically prone to cardiovascular disease (CVD) in a context of multimorbidity and geriatric syndromes. Risks include high susceptibility to functional decline, with many older adults tipping towards patterns of sedentary behavior and to downstream effects of frailty, falls, disability, poor quality of life, as well as increased morbidity and mortality even if the incident CVD was treated perfectly. While physical activity has been shown to moderate these patterns both as primary or secondary preventive medical care, the majority of older adults fail to meet physical activity recommendations. Clinicians of all specialities, including CVD medicine, can benefit from greater proficiency in functional assessments for their older adults, as well as from insights how to initiate effective functional enhancing approaches even in older adults who may be frail, deconditioned, and medically complex. Pertinent functional assessments include traditional cardiovascular metrics of cardiorespiratory fitness, as well as strength and balance. This review summarizes the components of a wide‐ranging functional assessment that can be used to enhance care for older adults with CVD, as well as interventions to improve physical function.